2012
DOI: 10.1111/j.1742-4658.2012.08529.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans: key players in cancer cell biology and treatment

Abstract: Glycosaminoglycans are natural heteropolysaccharides that are present in every mammalian tissue. They are composed of repeating disaccharide units that consist of either sulfated or non‐sulfated monosaccharides. Their molecular size and the sulfation type vary depending on the tissue, and their state either as part of proteoglycan or as free chains. In this regard, glycosami‐noglycans play important roles in physiological and pathological conditions. During recent years, cell biology studies have revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
425
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(449 citation statements)
references
References 175 publications
6
425
0
11
Order By: Relevance
“…As an enzyme that degrades hyaluronan, HYAL2 is known to be a tumor suppressor gene involved in cell adhesion, cell mobility, chemokinesis, cancer progression, angiogenesis and metastasis. [35][36][37][38][39] Our results also approved the tumor suppressor character of HYAL2 in tissue by observing higher HYAL2 methylation levels in malignant BC tumors than in benign breast tissues (Supporting Information Fig. 3).…”
Section: Discussionsupporting
confidence: 67%
“…As an enzyme that degrades hyaluronan, HYAL2 is known to be a tumor suppressor gene involved in cell adhesion, cell mobility, chemokinesis, cancer progression, angiogenesis and metastasis. [35][36][37][38][39] Our results also approved the tumor suppressor character of HYAL2 in tissue by observing higher HYAL2 methylation levels in malignant BC tumors than in benign breast tissues (Supporting Information Fig. 3).…”
Section: Discussionsupporting
confidence: 67%
“…It has been earlier reported that CSPG2 gene is upregulated in biopsy-proven NASH patients versus obese controls 44 . CS and HS were also implicated in cancer progression 45 , one of the most severe outcomes of NASH. Therefore, we predicted that these changes in gene expression, in particular as it involves complete metabolic pathways, may correlate with a change in blood concentration of the pathwayassociated metabolites.…”
Section: Article Nature Communications | Doi: 101038/ncomms4083mentioning
confidence: 99%
“…There are literally thousands of different HA sizes in remodeling microenvironments, including tumors. HA polymers bind to cells via at least six known receptors (16,19,20,(26)(27)(28)(29)(30)(31)(32). Two of these, cluster designation 44 (CD44) and receptor for HA-mediated motility/HA-mediated motility receptor (RHAMM/HMMR), form multivalent complexes with different ranges of HA sizes (19,29,33), and both receptors are implicated in BCa progression (19-21, 23, 29, 30, 33-36).…”
mentioning
confidence: 99%